Effects of 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chroman-4-one on serum levels of antioxidant enzymes in hyperlipidemic rats - . Prasetyastuti; Noviyanty Indjar Gama (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Hyperlipidemia triggers oxidative stress caused by an imbalance between oxidant and antioxidant levels due to the excess production of reactive oxygen species (ROS). The increase of ROS can decrease antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). 7-OH-2-(4-OH-3-Methoxyphenyl)-chroman-4-one is exogenous antioxidants isolated from mahogany seeds (Swietenia macrophylla King). This study aimed to evaluate the effects of the 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one on serum levels of SOD, CAT, and GPx in hyperglycemic rats. Thirty-six male Wistar rats (Rattus norvegicus) were divided into the following six groups: (N) normal group, (HL) hyperlipidemia group, (P) hyperlipidemia group with simvastatin, F10, F30, and F90 hyperlipidemia group with 7-OH-2-(4-OH-3-methoxyphenyl)-chroman-4-one 10, 30 and 90 mg/200g body weight (BW), respectively.  Hyperlipidemia was induced by feed enriched with cholesterol and cholic acid. Treatments were administered orally by gavages. After 4 weeks of treatments, blood sample was drawn and serum levels of SOD, CAT, and GPx enzymes were analyzed using a spectrophotometric method. Serum levels of SOD, CAT, and GPx in hyperlipidemic rats treated with 7-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-chroman-4-one at dose 10, 30 and 90 mg/200g BW were higher than HL group. In addition, no significantly different on serum SOD and CAT between group F90 and group P was observed (p>0.05)